Phosphatase SHP2 pathogenic mutations enhance activity by altering conformational sampling - Andrew W. Glaser; Ricardo A. P. Pádua; Adedolapo M. Ojoawo; Camille Sullivan; Dorothee Kern (Proceedings of the National Academy of Sciences, 2026)
SH2 domains are critical mediators of cellular signaling, although the molecular mechanisms by which they bind their phosphopeptide ligands remain incompletely understood. We investigate the atomic mechanisms underlying both healthy regulation and dysregulation of the human protein tyrosine phosphatase SHP2, a key regulator of cellular signaling. While most pathogenic mutations cluster near the PTP/N-SH2 interface, the E139D and T42A mutations are located within the regulatory SH2 domains, and their mechanisms of dysregulation remain controversial. The T42A mutation in the N-SH2 domain paradoxically increases phosphotyrosine-peptide binding affinity despite disrupting the hydrogen bond of T42 to the phosphoryl group, a puzzling contradiction that remains unresolved. We find that the T42A mutation shifts the conformational ensemble of peptide-bound N-SH2 toward a zipped β-sheet state and suppresses millisecond conformational exchange, supporting a model in which enhanced stabilization of the zipped conformation contributes to hyperactivation. This conformational shift provides a structural rationale for the increased affinity of T42A and helps reconcile previously conflicting models of peptide-induced SHP2 activation. By integrating X-ray ensemble refinement with NMR relaxation, our work illustrates how complementary structural and dynamic approaches can uncover regulatory mechanisms in SHP2 and may inform broader principles of SH2-mediated phosphopeptide recognition.